Xbox One - Roese, Neal J., (SAGE knowledge. Cases., 2016)
When the Xbox One console was officially revealed, Microsoft effectively confirmed that it would require an always-on connection for validating digital rights. Predictably, gamers reacted negatively, a response that was exacerbated when Microsoft's president of the interactive entertainment business, Don Mattrick, made dismissive statements about their concerns. This study examines how Microsoft dealt with the situation.